THE SUBJECT OF SOCIAL AND HUMANITIES COGNITION - S. Ya. PODOPRIGORA (Advanced Engineering Research)
Philosophical problems of social sciences and humanities in the aspect of person- 's subjectivity, life world, forming of values orientation, strategies of life cognition, self creation of person are studied in the article. It's shown that developing of synergetic problems results in reinterpreting of man's situation in the structure of cognition and practical activities. It enables to newly analyze social and humanities cognition.